Fungsi Humas dalam Menjalin Hubungan di Pemerintahan Kota Bukittinggi - Suci Wahyuni Multi; Usman Usman; Arina Fransiska (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The purpose of this study is to know the function of public relations in maintaining, maintaining internal and external relations within the city government Bukittinggi. The research was motivated by negative issues circulating from the public among the Bukittinggi city government. The achievements of the City Government of Bukittinggi in a short time together with the problems that came, such as the fire of the Pasar Atas trade center which is the economic hub of the city of Bukittinggi, the central convection fire market Aur Kuning which is the largest wholesale and retail navel in West Sumatra. This study uses descriptive qualitative research methods. Data collected in the form of words, pictures and script interviews, notes in the field, photos, personal documentation and other official documentation. The results of this study reveal that the Public Relations Section for the Government of the city of Bukittinggi is a very important and very necessary need in the government. Especially related to meeting the community's need for information. The function of public relations is to communicate and inform the public about work plans, performance, and results achieved by the government. And establish a harmonious relationship with various parties. The function of public relations in the Bukittinggi city government is also to absorb aspirations from public reaction